Use of nano-magnetic materials for removal of lead (II) and cadmium (ii) ions from aqueous solutions - Hammood, Ahmed Y.; Jassim, Tarik E.; Al-Asadi, Mohanad J.K. (Mesopotamian Journal of Marine Sciences, 2021)
Ferrite nanoparticles (NPs) with structure NiFe2O4 were created following the sol-gel auto-combustion method using lemon juice as surfactant and fuel agent. This method is located within the green chemistry, a method of environmentally friendly and less expensive than other methods. Nanomaterial’s have been diagnosed using different physical and chemical techniques: Brunauer-Emmett-Teller (BET) analysis, Field Emission-Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray Spectrosc0py (EDX), F0urier-Transform Infrared Spectroscopy (FTIR), Transmission Electr0n Microscopy (TEM) and X-ray diffraction (XRD). X-ray diffraction patterns confirmed the phase purity and the particle size 24.27nm. The effects of adsorbent concentration, pH, temperature, and time of contact on Lead and Cadmium ions uptake behavior were measured. The optimum time of contact to attain equilibrium is 60min for Lead (II) ion and 90 min for Cadmium (II) ion, and pH values are in the range (3-9). The results of adsorption showed a strong correlation with Freundlich model compared with the Langmuir model. The thermodynamic parameters were given, revealing endothermic reaction for ΔH, ΔG was found a spontaneous process and ΔS had positive value, increase of disorder of the process.